Exploitation of Hybrid Vigor for Identification of Promising Sorghum F1 Hybrid for High Grain Yield and Resistance to Sorghum Midge - Massaoudou Hamidou; Oumarou Souleymane; Mahamadou Salifou; Malick N. Ba; Issoufou Kapran; Vernon Gracen; Kwado Ofori; Eric Yirenkyi Danquah (International Journal of Agronomy)
Sorghum is the second most grown cereal crop in Niger. However, sorghum production in the country is dominated by indigenous cultivars with low productivity. Productivity in grain sorghum has been achieved in developing countries around the world using hybrids. This study was conducted to evaluate heterosis in F1 sorghum hybrids for grain yield and resistance to midge. Fifty F1 sorghum hybrids were evaluated for grain yield and resistance to midge. Variation for grain yield, midge resistance, and flowering time was observed. The magnitude of better parent heterosis for grain yield and resistance to midge varied significantly among hybrids. Four hybrids combined high better parent heterosis for both grain yield and resistance to midge while eight hybrids were better than their better parent for resistance to midge. These hybrids performed well for grain yield and/or resistance to midge. Therefore, the parental lines involved in these hybrids can be advanced for commercial hybrids production or used in sorghum improvement programs.